Wired/wireless internet communications : 12th International Conference, WWIC 2014, Paris, France, May 26-28, 2014. Proceedings - Fowler, Scott; Hoceini, Saïd; Daachi, Boubaker; Mellouk, Abdelhamid (Lecture Notes in Computer Science, 2014)
This book constitutes the thoroughly refereed post-conference proceedings of the 12th International Conference on Wired/Wireless Internet Communication, WWIC 2014, held in Paris, France, during May 27-28, 2014. The 22 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on wireless and wired networks; resource management and next generation services; next generation services, network architecture and applications.